Appendicitis in a Neutropenic Patient: A Multicentric Retrospective Study. Issue 5 (July 2017) - Scarpa, Alberto A.; Hery, Géraldine; Petit, Arnaud; Brethon, Benoit; Jimenez, Irène; Gandemer, Virginie; Abbou, Samuel; Haouy, Stéphanie; Breaud, Jean; Poiree, Marilyne
Abstract : To study the management of acute appendicitis in neutropenic patients, we retrospectively reviewed cases of acute appendicitis in neutropenic children treated for cancer. The patients' demographics, medical records, and outcomes were tracked. We compared nonoperative treatment versus emergency or delayed surgery. The cases of 30 patients with a mean age of 8.8 years in 12 French departments of Pediatric Hematology/Oncology between 1995 and 2013 were studied. Most patients (90%) were treated for hematological malignancies. Seven of the 30 children were successfully treated with exclusive medical treatment. Early surgery was performed in 6 patients, and the remaining 17 underwent combined management with a first-line antibiotic treatment and delayed appendectomy. Treatments were successful in all cases with transitory complications in only 3 patients. No death linked to infection was reported. Surgery was well tolerated even in the neutropenic period. Appendix perforation was a major risk factor of prolonged hospitalization. Histologic as well as bacteriologic and mycologic/parasitologic analyses were required in case of surgery. Analysis of diagnostic assessments showed the major importance of imaging (ultrasonography and tomography) on diagnosis confirmation. We could not come to a conclusion in the few numbers of reviewed cases because of a significant difference in management strategies, but we can conclude that early surgery after adequate supportive care is an acceptable modality of treatment and must be chosen in the face of life-threatening conditions.